The Feasibility Study on Using Indigo Residues from the Natural Dye Extraction Process to Produce Handicraft Paper - Leksuksri, Jarawee; Hongsri, Korpong; Ardsamang, Theerat (Bulletin of Applied Sciences, 2023)
Indigo (Indigofera tinctoria L.) is a shrub belonging to the Leguminosae family. It prefers sunlight and little water and mostly grows in the north and northeast of Thailand. Indigo is considered the well-known textile dye in textile industry due to its beautiful and durable color. After the production of dye color from the indigo, a large amount of indigo stem has been discarded as waste. This research thus aims to study the feasibility of using indigo residues from dye extraction process as raw material in handicraft paper production to reduce the amount of waste and add value to indigo stem waste. Indigo wastes after dye extraction was analyzed the chemical compositions and pulped by soda pulping process. The indigo pulp properties were further improved by beating. Then, handicraft sheets was formed and tested for the physical and optical properties. The paper bag packaging prototype was subsequently made from these indigo handicraft sheets. The results showed that the amount of holocellulose was 28.6% and lignin was 12.1%. The indigo pulp after soda pulping had 58.3% yields and had 190 mL CSF freeness after being beaten for 3 minutes. The pulp could be formed into handicraft paper without extra additives addition. The handicraft paper made from stem mixed with leave had tensile index of 9.63 Nm/g, tear index of 8.28 mN.m2/g and burst index 0.69 kPa.m2/g. The paper bag made from this handicraft paper could be used to carry the light-weighted item.